THE BEST FACTORS FOR INFLUENCE KNOWLEDGE SHARING AMONG TEACHERS THROUGH WEBSITE TECHNOLOGY - Rahmat Musfikar (UIN Ar-Raniry, 2017)
The purpose of this research is to answer the question and know the problems of implementation the knowledge sharing in an educational organization, that is in the school. This paper is will be explain the the best factors for implementation of knowledge sharing among teachers through website technology. this paper using research methods is study literature review. This researcher is using some previous research, using theoretical frameworks model and using existing research into knowledge management, the model has been constructed by combining, synthesizing and refactoring the factors, which have the most important effects in knowledge sharing using web technologies for the teacher. Knowledge Sharing and Total Quality Management, Enabler in the Knowledge Sharing Process, Investigation of Knowledge Sharing for Teachers, Knowledge Sharing Technology Model, Knowledge Sharing through ICT for Teachers, and Investigating Factors for Knowledge Sharing Using Web Technologies. This research is propose the best factor for successful implementation knowledge sharing among teacher are Task and Policy of Ministry of Education, individual, organization and technology